2014
DOI: 10.1242/jeb.101741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding on in vivo motility patterns in the proximal intestine of shorthorn sculpin (Myoxocephalus scorpius)

Abstract: This is the first study to catalogue the diverse array of in vivo motility patterns in a teleost fish and how they are affected by feeding. Video recordings of exteriorised proximal intestine from fasted and fed shorthorn sculpin (Myoxocephalus scorpius) were used to generate spatio-temporal maps to portray and quantify motility patterns. Propagating and non-propagating contractions were observed to occur at different frequencies and durations. The most apparent difference between the feeding states was that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(54 citation statements)
references
References 89 publications
6
48
0
Order By: Relevance
“…Recently, we described a diverse array of in vivo motility patterns in adult shorthorn sculpin (Myoxocephalus scorpius) for the first time (Brijs et al, 2014). Many of the motility patterns were reminiscent of, and/ or may have similar functions to motility patterns documented in other vertebrates (e.g.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Recently, we described a diverse array of in vivo motility patterns in adult shorthorn sculpin (Myoxocephalus scorpius) for the first time (Brijs et al, 2014). Many of the motility patterns were reminiscent of, and/ or may have similar functions to motility patterns documented in other vertebrates (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…To date, studies examining gastrointestinal motility in fish, including the effects of various neuropeptides and other signalling substances, have primarily used in vitro models (isolated segments of gut; Gräns and Olsson, 2011;Olsson and Holmgren, 2001). Only a few studies have examined the underlying in vivo control mechanisms (Brijs et al, 2014;Holmberg et al, 2007Holmberg et al, , 2006; Rich et al, 2013). Findings from some of these studies have revealed that although blockade of neural activity (using tetrodotoxin, TTX) abolishes some motility patterns, other patterns persist, indicating that they are myogenic in origin (Brijs et al, 2014;Holmberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations